Student Mobility in The Rising Peripheries - Theo, Rika (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
This research aims to investigate the different pattern of Chinese Indonesian student mobility following three main political sequences defined by not only different period but also the dominant mode of each time. The object of this research is Chinese Indonesian student. Using historical comparative analysis, this paper explores and compares the historical trajectory of transnational mobility of Indonesian students to China. In every sequence, the particularÂ mobility patternÂ of Chinese-Indonesian students will be analyzed in relation to national politics within certain bilateral and global framework. Drawing on the comparative historical analysis, this research explores how a specific sequence affects specific student mobility between Indonesia and China. The analyses go further to investigate the continuity between sequences, the linkages between the past mobility to a contemporary one. Building on these analyses, this research argues that nation-states policies and trans-state relation that develop overtime play a significant role in defining Indonesian student mobility to China.